Convergence, Accommodation, Fusion, and Stereopsis: What Keeps the Eyes Aligned in Intermittent Exotropia?. (26th July 2018) - Schiavi, Costantino; Di Croce, Valentina; Primavera, Laura; Tassi, Filippo
Abstract : Purpose . To investigate the relationships between angle of deviation, fusional convergence and divergence amplitude, AC/A ratio, near point of convergence (NPC), and myopia-phoria in intermittent exotropia (IXT). Methods . 93 patients with IXT, divided into two groups, were recruited in the study. In Group A (73 patients), fusional convergence and divergence amplitudes, NPC, and AC/A ratio were studied and compared with a control group. In Group B (in 20 patients), myopia-phoria while switching from monocular to binocular view was studied with an infrared video retinoscopy and compared with a control group. Results . In Group A, positive fusional amplitudes, NPC, and AC/A ratio of IXT patients did not differ from those of normals. Negative fusional amplitudes were significantly higher in the patient group than in the control group. In Group B, myopic shift was statistically significantly higher in the patient group and there was a statistically significant positive correlation between myopic shift and angle of strabismus. Conclusions . Apart from the role of fusional convergence which accounts for myopia-phoria, that of the other binocular functions in the control at near of IXT and conversely their specific role in the pathogenesis of IXT remain unclear and the cause of divergent infantile strabismus is still unknown.